Analisis Implementasi Pemanfaatan Lingkungan Sekolah untuk Motivasi Belajar Siswa MI Mata Pelajaran IPA Materi Lingkungan - Rosyidah, Af'idatur; Choiriyah, Ma’rifatul; Kurniawati, Siti; Suttrisno, Suttrisno (Prodi PGMI STAI Al-Akbar Surabaya, 2024)
Student motivation to learn is often the main challenge in the learning process, seen from students' lack of attention to the material presented, low active participation, and reluctance to complete assignments. Effective education requires a creative, active, and contextual approach to creating meaningful learning experiences. One potential approach is to utilize the school environment as a learning resource. The school environment, such as parks, gardens, play facilities, and other elements, can be a real and contextual learning medium, allowing students to connect theory with practice. This research aims to analyze the implementation of the use of the school environment in increasing MI students' learning motivation in science subjects, especially environmental material. This research uses a qualitative method with a phenomenological approach, where data is collected through literature studies from various sources such as books, journals and scientific articles. The research results show that the school environment can be used to improve students' cognitive, affective and psychomotor skills, while making learning more enjoyable and effective. Environment-based learning also helps students understand science material, such as healthy and unhealthy environments, more easily. However, there are challenges in its implementation, such as limited school facilities and lack of teacher creativity. This research recommends strategies to maximize the positive impact of using the school environment in supporting student learning motivation holistically.